Proposed Dashboard Concept for TUS MART: Enhancing Aquaponic and Hydroponic Sales Management Using the Innovation Canvas Method - Putra, Perdana Suteja; Zunaidi, Rizqa Amelia; Hidayati, Sri; Mardhiana, Hawwin; Chandra, Huki; Novika, Norma (Sistemasi: Jurnal Sistem Informasi, 2024)
The rapid evolution of e-commerce has transformed agricultural operations, prompting Telkom University Surabaya to develop TUS MART, an e-commerce platform designed for managing and selling aquaponic and hydroponic products cultivated by the university. However, TUS MART faces challenges such as inadequate data management, limited user interface intuitiveness, and inefficiencies in sales tracking and customer relationship management. This research proposes a comprehensive dashboard for TUS MART, developed using the Innovation Canvas Method, which aligns with both user needs and business objectives. The methodology involved phases like "Explore," "Ideate," "Market," "Design," and "Value Proposition," ensuring that the dashboard meets essential performance standards while addressing critical risks. The resulting dashboard enhances real-time inventory tracking, sales analytics, and customer management, contributing to TUS MART’s operational efficiency, sustainability, and educational objectives. This study highlights the successful application of innovative design frameworks in developing user-centered e-commerce solutions that integrate technological and agricultural advancements.